Ghanaian midwifery students' perceptions and experiences of disrespect and abuse during childbirth - S Rominski, MPH (Elsevier, 2015)
Background: One strategy to reduce maternal and neonatal mortality in low-income and middle-income countries is to increase the rate of deliveries in health clinics and hospitals. However, reports of disrespect and abuse of women during birth are becoming common. When women are disrespected or abused during childbirth, they are less likely to choose facility-based births in the future. We did an exploratory qualitative study to investigate midwifery students' experiences and perceptions of how women are treated during labour and delivery. Methods: Final year midwifery students (n=160) from Ghana's 16 public midwifery training colleges were invited to participate in a focus group at their institution. Students were asked to describe disrespect and abuse of women that they had observed, and about their definitions of respectful patient care and the consequences of disrespectful and abusive practices by health-care providers. Focus groups were conducted in English by the study team, tape recorded, and transcribed verbatim. Findings: Student midwives reported that they had seen high levels of disrespect and abuse during their training. They discussed the consequences of disrespect and abuse and spoke of what respectful patient care meant to them; that is, treating every patient with respect, regardless of her background or ability to pay. While participants agreed that respectful care is important, they were also able to justify disrespectful or abusive practices they had witnessed or participated in themselves. For example, one student said, "the health of the child was at risk because of her attitude. To save the child, or to save the infant, she was being yelled at to push. To me, she understood the reasons why she was being yelled at to push because if not so, definitely it would have ended in a stillbirth." Interpretation: While student midwives understand the reasons why respectful care is important, they believe that there are instances where abusive behaviour is necessary to ensure both the woman and her child survive childbirth. Midwives in training could benefit from increased training on ways to communicate with and motivate women during labour and delivery. Funding: This project was funded by the African Studies Center, University of Michigan.